A study on participatory management and conservation of mangrove ecosystem in Matang and Carey Island, Malaysia / Mehdi Almasi - Mehdi , Almasi (2018)
Management of mangrove forests is vital, especially for the conservation and revival of mangrove resources. Community-based mangrove forest management with involvement of various stakeholders could be an effective way for the conservation of the rich ecosystem of mangrove forests. The present research aims to formulate a participatory management strategy to conserve mangrove forests in the Matang Mangrove Forest and Carey Island in Malaysia as the participatory approach in management has not been well addressed in the literature on mangrove forest management in this country. The major management tool is a SWOT matrix analysis. For this purpose, the analysis of the data collected from in-depth interviews (31 for the Carey Island and 35 for Matang) with local people living in both areas of research as well as the information from the researchers’ observation resulted in identification of a series of internal and external factors in the targeted areas in terms of conservation of the mangrove forest. The factors were then scored using a SWOT questionnaire filled by respondents (312 for the Carey Island and 377 for Matang). Resulting in sixteen strategies (for both research areas) were considered using SWOT matrix and pairwise matching for the conservation of the mangrove forests. Later, the Quantitative Strategic Planning Matrix (QSPM) was used and prioritized strategies were determined. As a conclusion, the prioritized strategies in the Carey Island were all related to capacity building, involvement and participation of stakeholders in the process of the mangrove forest conservation. Therefore, mangrove forest management requires a participatory approach in a way that not only the mangrove harvesting would be sustainably controlled, but stakeholders, especially villagers, will be simultaneously empowered and take responsibility of the sustainable conservation of their habitat and its biodiversity. In the Matang Mangrove Forest, it was concluded that participation of local communities in the management of the Mangrove forest is the key element of the priority strategies.